2004
DOI: 10.1104/pp.103.033415
|View full text |Cite
|
Sign up to set email alerts
|

Homology Modeling of Representative Subfamilies of Arabidopsis Major Intrinsic Proteins. Classification Based on the Aromatic/Arginine Selectivity Filter

Abstract: Major intrinsic proteins (MIPs) are a family of membrane channels that facilitate the bidirectional transport of water and small uncharged solutes such as glycerol. The 35 full-length members of the MIP family in Arabidopsis are segregated into four structurally homologous subfamilies: plasma membrane intrinsic proteins (PIPs), tonoplast intrinsic proteins (TIPs), nodulin 26-like intrinsic membrane proteins (NIPs), and small basic intrinsic proteins (SIPs). Computational methods were used to construct structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
196
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 199 publications
(204 citation statements)
references
References 43 publications
5
196
1
2
Order By: Relevance
“…On the contrary, the ar/R region of AtTIP5;1 is unique. Because of this, AtTIP5;1 would have a larger apparent pore aperture and a reduced ability to form hydrogen bonds with transported solutes [26]. Therefore, AtTIP5;1 may have transport properties that are unlike conventional aquaporins, although we showed here that AtTIP5;1 transports water and specifically urea, since no transport of glycerol or boric acid was observed.…”
Section: Materials Injectedmentioning
confidence: 61%
“…On the contrary, the ar/R region of AtTIP5;1 is unique. Because of this, AtTIP5;1 would have a larger apparent pore aperture and a reduced ability to form hydrogen bonds with transported solutes [26]. Therefore, AtTIP5;1 may have transport properties that are unlike conventional aquaporins, although we showed here that AtTIP5;1 transports water and specifically urea, since no transport of glycerol or boric acid was observed.…”
Section: Materials Injectedmentioning
confidence: 61%
“…In contrast, NIP II proteins, which differ principally at one residue within the aromatic/arginine selectivity filter, show little water permeability (17,19) but do transport a variety of uncharged solutes, including glycerol and urea (17), as well as metalloid compounds, including boron and silicon (19,20). With respect to pore determinant sequences, AtNIP2;1 resembles the nodulin 26-like NIP I pore group (9), showing the conserved aromatic/arginine selectivity sequence of this group. Nevertheless, the results of the present study show that AtNIP2;1 is clearly distinct from nodulin 26 and other NIP I proteins, such as AtNIP1;1 and -1;2 (10, 11), not only in its ability to transport lactic acid instead of glycerol but also in its unusually low permeability to water.…”
Section: Discussionmentioning
confidence: 99%
“…As pointed out previously, the pore properties and multifunctional transport signature of this subfamily of plant MIPs are unique (15). Based on modeling, there are two general pore subfamilies of NIP, NIP I and NIP II (9). NIP I proteins are typified by soybean nodulin 26 and form aquaglyceroporins that transport glycerol as well as water (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that several NIPlike mutants of both the NIP I and NIP II ar/R subclasses show the ability to complement yeast ammonia auxotrophs but that this ability also depends upon additional residues in other regions of the pore [20]. In the present study it is shown that purified soybean nod26, the NIP family archetype which has an ar/R region characteristic of NIP I pores [22], exhibits the ability to transport NH 3 and shows an approximately fourfold stronger preference for this substrate over water. Additionally, the use of purified nod26 liposomes allowed a determination of the single channel rate for ammonia transport.…”
Section: Discussionmentioning
confidence: 66%